Intelligent School Computer Laboratory Reservation System by Using Multiple Agents Based - Sulaiman, Mahzan (2009)
One of the problems about school computer laboratory is to handle the reservation for class subject (non-computer based relation) or any events in Malaysia. The reservation process was still using manual approach. To make reservation, a user must fill the form; meet the administrator to check lab availability and lastly the admin will approve it. A computer system must be developed to manage the reservation for user request. This system was used multiple intelligent agents that assist the user and the admin to manage the lab reservation based on a few constraints such as holiday and permanent classes. The agents also try to give alternative session if the request session is not available. The agents have ability to evaluate user authentication based on inconsistent action on the system and will keep up the security level based on individual authentication. The collection of user action pattern is recorded then gives direction to the agent to reconstruct its intend action related to user behavior. FIPA-ACL as communication standard between the agents to make them able to be socializes in their environment. This system was developed by using JAVA computer programming language. JAVA programming is the best choice to create multi-agent functions and reacted base on intelligent agents approach. The system will be deployed as a stand-done system and also might share through internal local area network (LAN). MS Access was used as the database for storing the data and might it easy to integrate with Education Management Information System (EMIS) that already exist. The level of user' acceptance was determined using Technology Acceptance Model (TAM) by Davis (1989) where data is gathered through a set of designed questionnaire. In conclusion, this system has a great potential to encounter school computer lab reservation problem by using intelligent multi-agent as human behalf.